2018
DOI: 10.17816/ecogen16160-69
|View full text |Cite
|
Sign up to set email alerts
|

Association between cytokine gene polymorphisms and squamous cell lung cancer depending on the duration of smoking in men

Abstract: Background. Squamous cell lung cancer (SCLC) is the most common form of lung cancer among men smokers. Mediators and products of inflammation can contribute to the initiation of carcinogenesis in smokers. The aim of study is to investigate the association between IL1B(rs1143634, rs16944), IL1RN (rs2234663), TNFA (rs1800629), IL6 (rs1800795), IL10 (rs1800896) genes and SCLC depending on the duration of smoking in men. Materials and methods. We studied 324 patients with SCLC and 168 healthy men smokers. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Figure 1 outlines the complete study selection process in this meta-analysis. Forty-four studies 17 , 25 67 were selected from 970 primary studies acquired from the searched databases following the eligibility criteria. Comprehensive screening of the titles, abstracts and full texts for each study was conducted to include or exclude the studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 outlines the complete study selection process in this meta-analysis. Forty-four studies 17 , 25 67 were selected from 970 primary studies acquired from the searched databases following the eligibility criteria. Comprehensive screening of the titles, abstracts and full texts for each study was conducted to include or exclude the studies.…”
Section: Resultsmentioning
confidence: 99%
“… 34 , 53 This SNP did not show any association with NSCLC and small cell lung cancer in men. 29 , 35 , 41 For CRC, only polymorphism carriers among the Chinese Han population showed an increased risk, 56 but other studies reported a negative association. 44 , 64 Patients with MM carrying CT and TT alleles of the IL-1β +3954C>T polymorphism exhibited improved survival rates and survival conditions compared with the CC allele carriers.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that their carriers are more likely to suffer from liver diseases [16] and have an increased risk of tuberculosis [15,17]. Allele -174G is considered a risk factor for squamous cell lung cancer and chronic obstructive pulmonary disease [18], cancer and fundic atrophy of the stomach [19], ovarian cancer [20], intrauterine infection of the fetus [21], development of cerebral arteriovenous malformation [22] and is associated with the risk of developing type 2 diabetes [23,24]. Allele -572С has also been associated with ischemic stroke in indigenous West African men [25].…”
mentioning
confidence: 99%